Thoracic spinal thrust manipulation for shoulder impingement syndrome: A meta-analysis of pain relief and functional outcomes - Bazal Bukhari; Ali, Sarwat; Saba Afzal (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the effectiveness of thoracic spine thrust manipulation in managing shoulder impingement syndrome. Method: The meta-analysis was conducted from April 25 to November 5, 2023, after approval from the ethics review board of the University of Lahore, Lahore, Pakistan, and comprised a comprehensive search on multiple databases, including Cochrane Central Register of Controlled Trials PubMed, PEDro and MEDLINE. Randomised controlled trials with patients of either gender aged 19-44 years who had been diagnosed with shoulder impingement syndrome were included. Data extraction was independently performed by two researchers, and meta-analysis was conducted using RevMan 5.2. Results: Of the 14 studies comprising 749 participants, 8(57.14%) studies comprising 410(54.73%) participants involved quantitative analysis. The fixed-effect model revealed minimal heterogeneity (I2=0%) and a standardised mean difference of -0.03 (95% confidence interval: -0.22-0.16), indicating no significant improvement in clinical outcomes following thoracic spinal thrust manipulation. Conclusion: The meta-analysis provided a more complex view of the efficacy of thoracic spinal thrust manipulation in treating shoulder impingement syndrome. Some researchers suggested that treatment by manipulation positively affected immediate changes in range of motion and pain, while others revealed no significant clinical changes. This indicates the need for the application of manipulation alongside other exercise therapies for functional changes to be observed clinically. Key Words: Rotator cuff impingement, Rotator cuff impingement syndrome, Shoulder impingement, Shoulder impingement syndromes, Spinal manipulation.